Fragility analysis of self-centering prestressed concrete bridge pier with external aluminum dissipators. Issue 8 (August 2017) - Cao, Zhiliang; Wang, Hao; Guo, Tong
A novel self-centering prestressed concrete pier with external energy dissipators has been developed to realize seismic resilient performance and enhanced corrosion-resisting property. Self-centering capacity of the pier is provided by the unbonded post-tensioned tendons and damage is mostly concentrated on the replaceable dissipators. To investigate the seismic behavior of the proposed pier, a detailed analytical model considering interface opening and dissipator deformation was developed and verified through existing cyclic load tests. Based on the proposed model, a prototype reinforced concrete pier and a self-centering prestressed concrete pier with similar backbone curves are designed, and fragility analyses are conducted on the two piers through incremental dynamic analysis. One maximum drift-based performance limit state (i.e. collapse prevention) and two residual drift-based performance limit states (i.e. emergent usage and reconstruction) are defined for seismic capacity evaluation. Fragility curves indicate that the self-centering prestressed concrete pier has a slightly higher peak drift demand owing to its inferior dissipating capacity as compared with the reinforced concrete pier, while sustains a much lower residual drift demand due to its inherent self-centering characteristic.